2016
DOI: 10.1177/0272431616642324
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Violence and Sexual Risk Among Early Adolescents in Urban Middle Schools

Abstract: This article examines the relationship between exposure to violence, fear of exposure to violence, and sexual risk among a sample of urban middle school youth. The sample included 911 seventh-grade students who completed self-report surveys. Approximately 20% of the sample reported at least one direct threat or injury with a weapon in the past 3 months, and 52% reported ever seeing someone seriously injured or killed. Experiencing a direct threat was significantly associated with greater intentions to engage i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 43 publications
2
4
0
Order By: Relevance
“…Consistent with previous research, this study found that there was an association between bullying and HIV risk . Previous studies on bullying have established that students who experience bullying are faced with trauma and use sex to cope with the victimization . As students engage with multiple sexual partners, they are bound to be exposed to HIV .…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with previous research, this study found that there was an association between bullying and HIV risk . Previous studies on bullying have established that students who experience bullying are faced with trauma and use sex to cope with the victimization . As students engage with multiple sexual partners, they are bound to be exposed to HIV .…”
Section: Discussionsupporting
confidence: 88%
“…The data reported here has shown that violencerelated behavior is also significantly associated with exposure to sex. This finding is in agreement with a study on the influence of exposure to violence on sexual risk among early adolescents 21 . From the study, adolescents experiencing a direct threat was significantly associated with a greater intention to engage in vaginal intercourse and sexual touching while witnessing violence alone is significantly associated with sexual touching 21 .…”
Section: Resultssupporting
confidence: 93%
“…By middle adolescence, most young people have been involved in at least one romantic relationship [2], a context associated with greater odds of sexual intercourse [3] and in which most sexual interactions occur [4]. Research suggests adolescents lack positive models as well as norms and skills related to building healthy relationships [5]. Nonetheless, developmental psychologists emphasize that adolescence represents a new period in which past models of relationships may be reshaped, priming young people for healthier adult relationships [6].…”
Section: Background and Rationalementioning
confidence: 99%
“…Indeed, some contextual factors, such as experience with romantic relationships or even exposure to violence, place adolescents at greater risk for engaging in sexual activity, including unprotected (eg, condomless) sex that could lead to an unplanned pregnancy or STI. In addition, exposure to violence, both directly and indirectly, is associated with risky behaviors (eg, unprotected sex), lack of self-efficacy, anxiety, depression, challenges developing and maintaining healthy relationships with prosocial peers, and increased associations with peers who endorse unsafe norms and behaviors [ 5 , 15 ]. Estimates suggest that 60% of children and adolescents younger than 18 years have been exposed to at least one form of violence in the previous year [ 16 ], meaning these adolescents are at increased vulnerability for other poor outcomes.…”
Section: Introductionmentioning
confidence: 99%